Guidelines for the digestive enzymes inhibition assay. Issue 5 (4th September 2022) - Wang, Jing; Zhao, Minjie; Liu, Tao; Feng, Fengqin; Zhou, Aicun
Abstract: As digestive enzymes play a key role in the digestion and absorption of nutrients, more and more studies have focused on the inhibitory effect of various biochemicals on digestive enzymes, such as amylase, glucosidases, lipases, and proteases, etc. Presently, assays were developed to evaluate the inhibitory activity of digestive enzymes vary. Therefore, to facilitate the study of digestive enzyme inhibitory activity, it is critical to select an adequate assay. In this guideline, assays used recently were selected for extended discussion, including the reaction systems of each assay as well as the practice of digestive enzymes inhibition assessment. Abstract :